Influence of the Characteristic Processes of the area of mathematics on the academic performance in the Educational Institution "Juan Mejía Baca" Chiclayo. - Zuloeta Salazar, José Félix (2018)
The present research work was carried out in the Educational Institution "Juan Mejía Baca", Chiclayo. The study was carried out with a sample of 25 women and 27 males of the third grade of secondary, with an age ranging from 13 to 16 years. The type of research according to the purpose it pursued was basic and according to the design, non-experimental transectional correlational / causal. The study was based on determining the influence of the processes characteristic of the area of mathematics on the academic performance in the subject of mathematics. These processes were dimensioned in four independent variables; Considering the academic performance in the math subject as a dependent variable. The academic achievement in the math subject was obtained by averaging the grades for each of the four semesters. The results obtained from the parametric analysis, through correlation and multiple regression, found that the processes or variables handling algorithms and solving problems in that order had a significant influence on academic performance. Multiple regression analysis confirmed that for each point of increase in the algorithm management test, academic performance increased by 0.636 points and for each point of increase in problem resolution academic performance increased by 0.277 points.  Key words: Correlation, regression, characteristic processes.